Trends in SDLC Document Review using Generative AI - Prashant Gulave,; Dr. Kavita Moholkar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This research paper explores the evolving role of Generative AI in Software Development Life Cycle (SDLC) document review. With AI-driven advancements in Natural Language Processing (NLP), models such as GPT, BERT, and domain-specific LLMs have been adapted to evaluate requirement specifications, test plans, and design documents. We present an analysis of how these models are being fine-tuned for document validation, compliance checking, and contextual feedback generation in the software industry. The paper also examines the integration of rule-based methods with AI, providing structured feedback for engineering domain documentation. Furthermore, we discuss emerging trends, challenges, and future research directions for enhancing AI-based document review in SDLC.
Keywords: Generative AI; SDLC; Document Review; Large Language Models; NLP